Internal medicine issues in palliative cancer care - Hui, David, 1975-; Bruera, Eduardo (Oxford University Press, 2014)
"Patients with advanced cancer may develop a number of clinical complications related to tumor progression or a variety of aggressive treatments. The majority of these patients are elderly, often with multiple co-morbidities that require appropriate assessment and management. In the palliative stage of their disease, patients undergo a progressive transition from active acute care to community-based hospice care. This transition requires modification in the diagnostic tests, monitoring procedures and pharmacological treatments to adjust them to the palliative and short-term nature of the care. Internal Medicine Issues in Palliative Cancer Care looks at internal medicine through a prognosis-based framework and provides a practical approach to maximizing comfort and quality of life while minimizing aggressive investigations and therapies for patients with life-limiting disease. Forty-six common internal medicine conditions are organized into nine clinical categories: pulmonary, cardiovascular, renal and metabolic, gastrointestinal, hematologic, infectious, endocrine, rheumatologic, and neuro-psychiatric"--Publisher's description